Analisis Kualitas Pelayanan, Tata Kelola, dan Peran Sumber Daya Perekaman E-KTP terhadap Kepuasan Masyarakat Kecamatan Labang: Analysis of Service Quality, Governance, and the Role of E-KTP Recording Resources on Community Satisfaction Labang District - Tri Risqiyana; Hurian Kamela (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
E-KTP recording services are a form of public service that is directly related to the administrative needs of the community. Service quality, governance, and the role of human resources are important factors in increasing public satisfaction with the services provided. This study aims to determine the influence of service quality, governance, and the role of E-KTP This quantitative study involved 100 respondents from Labang District. Data were analyzed using multiple linear regression, validity, reliability, classical assumption, t-, and F-tests with SPSS version 30. The results showed that service quality, governance, and human resource roles each had a significant partial effect on community satisfaction.